2017
DOI: 10.1038/srep42782
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of 19 X chromosome STR loci for forensic purposes in four Chinese ethnic groups

Abstract: A new 19 X- short tandem repeat (STR) multiplex PCR system has recently been developed, though its applicability in forensic studies has not been thoroughly assessed. In this study, 932 unrelated individuals from four Chinese ethnic groups (Han, Tibet, Uighur and Hui) were successfully genotyped using this new multiplex PCR system. Our results showed significant linkage disequilibrium between markers DXS10103 and DXS10101 in all four ethnic groups; markers DXS10159 and DXS10162, DXS6809 and DXS6789, and HPRTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…China, composed of 56 officially recognized ethnic groups and a population over 1,404 billion, harbors substantial genetic, linguistic, physical, cultural and diversity [ 30 , 31 ] (1.2 billion Hans, 10.5 million Huis, 10 million Uyghurs, 9.4 million Miaos, 8.7 million Yis, 6.2 million Tibetans, 1.4 million Lis, 1.4 million Kazakhs, 0.55 million Gelaos, 0.19 million Xibes, and others ( https://en.wikipedia.org/wiki/Han_Chinese ). Here, to implement X-STR typing into routine forensic practice and establish Chinese reference database as well as investigate genetic diversity and forensic characteristics of Han Chinese population, we newly generated 19 X-STRs data from 206 Guizhou Han subjects ( S1 Table ) and combined previously published 4868 genotypes [ 19 27 , 29 ], the dataset from 20 Chinese populations belonging to four language families: Sino-Tibetan includes Sinitic branch (Han [ 22 , 25 , 26 ] and Hui [ 25 ]) and Tibeto-Burman branch (Tibetan [ 20 , 25 , 27 ], Yi [ 19 ]); Tai-Kadai (Gelao, Li); Hmong-Mien (Miao [ 29 ]); Altaic comprises Turkic (Uyghur [ 20 , 21 , 25 ], Kazakh [ 23 ]), Tungusic (Xibe [ 24 ]). To characterize the genetic diversity of Han Chinese population, we then obtained 1344 genotypes of 19 X-chromosomal STRs in Han Chinese population from four different geographical administrations (Guizhou: 206, Sichuan [ 22 ]: 201, Hainan: 155, Guanzhong [ 26 ]: 474 and South China [ 25 ]: 308).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…China, composed of 56 officially recognized ethnic groups and a population over 1,404 billion, harbors substantial genetic, linguistic, physical, cultural and diversity [ 30 , 31 ] (1.2 billion Hans, 10.5 million Huis, 10 million Uyghurs, 9.4 million Miaos, 8.7 million Yis, 6.2 million Tibetans, 1.4 million Lis, 1.4 million Kazakhs, 0.55 million Gelaos, 0.19 million Xibes, and others ( https://en.wikipedia.org/wiki/Han_Chinese ). Here, to implement X-STR typing into routine forensic practice and establish Chinese reference database as well as investigate genetic diversity and forensic characteristics of Han Chinese population, we newly generated 19 X-STRs data from 206 Guizhou Han subjects ( S1 Table ) and combined previously published 4868 genotypes [ 19 27 , 29 ], the dataset from 20 Chinese populations belonging to four language families: Sino-Tibetan includes Sinitic branch (Han [ 22 , 25 , 26 ] and Hui [ 25 ]) and Tibeto-Burman branch (Tibetan [ 20 , 25 , 27 ], Yi [ 19 ]); Tai-Kadai (Gelao, Li); Hmong-Mien (Miao [ 29 ]); Altaic comprises Turkic (Uyghur [ 20 , 21 , 25 ], Kazakh [ 23 ]), Tungusic (Xibe [ 24 ]). To characterize the genetic diversity of Han Chinese population, we then obtained 1344 genotypes of 19 X-chromosomal STRs in Han Chinese population from four different geographical administrations (Guizhou: 206, Sichuan [ 22 ]: 201, Hainan: 155, Guanzhong [ 26 ]: 474 and South China [ 25 ]: 308).…”
Section: Resultsmentioning
confidence: 99%
“…We used the Reynolds’s and Nei’s pairwise genetic distances, as well as Fst and corresponding p values to estimate the genetic differences and similarities using the PHYLIP version 3.5 packages [ 40 ] and Arlequin software (version 3.5.2) [ 32 ]. We first compared the genetic relationships of Guizhou Han and other four Han Chinese populations from different geographical regions [ 22 , 25 , 26 ] as well as other 15 Chinese previously published minorities [ 20 , 21 , 23 25 , 27 29 ]. And then we investigated the genetic relation between the Meta-Han and other 15 reference populations [ 19 27 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…And Yang et al had indicated it could be used as a supplementary tool in kinship tests in China (Yang et al 2016). Further, genetic polymorphisms of this X-STR system have been investigated in a number of populations (Liu et al 2017;Meng et al 2017;Yang et al 2017;Zhang et al 2016). In the present study, we used this 19 X-STR multiplex PCR system to obtain genetic information from Western Mongols, including the allele frequencies and forensic parameters of these 19 X-STR loci, the haplotypic diversities of 7 X-STR linkage groups.…”
Section: Introductionmentioning
confidence: 99%
“…), Kazak(Liu et al 2017), Inner Mongolian(Tao et al 2018), Japanese(Uchigasaki et al 2013), Shanghai Han(Zhang et al 2012), Bhil(Shrivastava et al 2015), Malay(Samejima et al 2012), Taiwanese(Chen et al 2014), Ili Uygur(Guo et al 2016), Guanzhong Han(Zhang et al 2016), Tibetan(Yang et al 2017), Southern Han(Yang et al 2017), Hui(Yang et al 2017) and Korla Uygur(Yang et al 2017). For a better understanding, the geographical PeerJ reviewing PDF | (2017:09:20809:2:1:CHECK 4 Jun 2018)…”
mentioning
confidence: 99%